Genetic frequencies of paraoxonase 1 gene polymorphisms in Croatian population - Grdić, Marija (Array, 2008)
Summary: Paraoxonase 1 (PON1), a HDL-associated enzyme, is believed to contribute to the protective effects of HDL by decreasing the generation of lipid peroxidation products during the process of LDL oxidation. It has been reported that polymorphisms in promoter and coding regions of the pon1 gene could affect PON1 activity. The aim of this study was to determine the frequencies of pon1 polymorphisms Q192R, L55M and –108C>T and their influence on PON1 activity in healthy population of Croatia. The following genotype frequencies were determined: 60 % QQ, 34 % QR, 6 % RR for Q192R; 44 % LL, 43 % LM, 13 % MM for L55M; 30 % CC, 48 % CT, 22 % TT for –108C>T polymorphism. Genotypes RR, LL and CC were found to be associated with higher PON1 activity. The most frequent genotypes in healthy Croatian population were QQ, CT and equally present LL and LM